The identification of Rana ocellata Linnaeus, 1758: Nomenclatural impact on the species currently known as Leptodactylus ocellatus (Leptodactylidae) and Osteopilus brunneus (Gosse, 1851) (Hylidae) - Lavilla, Esteban Orlando (2010)
The usage of the name Rana ocellata Linnaeus, 1758, is plagued by misidentifications and misinterpretations. After an exhaustive bibliographic review, we conclude that the Linnaeus 1758 name refers to Osteopilus brunneus (Gosse, 1851) from Jamaica, while the taxon currently known as Leptodactylus ocellatus corresponds to Rana latrans Steffen, 1815. Herein, we designate and provide descriptions of the neotypes of Leptodactylus latrans (Steffen, 1815), revalidated, new combination, and Osteopilus ocellatus (Linnaeus, 1758), new combination, as a senior synonym of Osteopilus brunneus (Gosse, 1851).